Comparison between food frequency questionnaire and 24-hour dietary recall or weighing methods in evaluating dietary nutrient intakes of pregnant women - Zhang, Jing; Yu, Jiangfan; Duan, Yifan; Yang, Zhenyu; Bi, Ye; Zhang, Yuwen; Liu, Changqing; Zhao, Yongli; Gu, Xuyang; Gao, Jianghua; Duan, Jingtao; Lai, Jianqiang; et al. (Wei sheng yan jiu, 2025)
This study aimed to compare the similarities and differences among Food Frequency Questionnaire(FFQ), 24-hour dietary recall method, and weighing method in assessing the intakes of foods, energy, and nutrients in pregnant women, and to evaluate the validity of the FFQ. From June to September in 2017, a total of 82 pregnant women were recruited across the entire Wuqiang County in Hebei Province. The subjects were surveyed using the FFQ for the most recent week, 24-hour dietary recall for 3 consecutive days, and in-home weighing for 3 consecutive days. The differences in the average daily intakes of food, energy, and nutrients obtained by the FFQ and the other two method were calculated and compared. The correlation and consistency between the FFQ and the other two method were evaluated through the Spearman correlation coefficient and the Bland-Altman plot, respectively. There was no statistically significant difference between the FFQ and 24-hour dietary recall method in assessing the average daily intakes of